Corporate governance: Exploring the changing governance control paradigm and its implications for internal auditing - Christopher, Joseph (LaTrobe University, 2012)
Agency theory underpins the concept of governance and the role of internal auditing. Recent studies question both the legitimacy and practicality of an agency oriented governance paradigm in determining an organization’s control paradigm, arguing instead for a multi-theoretical approach to governance. This study explores this multi-theoretical proposition with a number of public universities throughout the world using a multiple case study approach to illustrate the concept of the changing control paradigm and its implications for internal auditing. The findings illustrates that the governance of public universities are informed by multiple theories and suggests that the theoretical foundation of internal audit should now also be aligned with a multi-theoretical approach to governance to achieve its role of enhancing governance. The study provides opportunities for further research with other industry sectors to explore the findings that have policy implications for redefining the governance control paradigm and theoretical foundations of control monitoring functions such as internal audit.